Relaxation dynamics of ferromagnetic FePt thin films in a broad frequency range - Alvarez, Nadia Roxana (2013)
The dynamical behaviour of FePt thin films in the chemically disordered fcc phase has been studied using ferromagnetic resonance spectroscopy in a broad range of frequencies, from 1 to 100 GHz. A set of samples with thicknesses between 9 and 94 nm was investigated at room temperature in order to analyse the damping of the magnetization as a function of the excitation frequency. As expected, the increase in frequency is accompanied by larger resonance fields and linewidths. These two quantities also display an anisotropic response when the external applied field is rotated from the in-plane to the out-of-plane direction. We have observed that in the thicker samples the linewidth is different for fields applied parallel or perpendicular to the film plane which, in principle, should not occur in homogeneous ferromagnetic films. This behaviour could be understood by the presence of a frequency-independent anisotropic inhomogeneous broadening that depends on film thickness, in addition to the Gilbert damping term (α) which gives a linear frequency dependence. Although this last term is in general isotropic, we have measured different values of α for in-plane (α = 0.025(1)) and out-of-plane (α⊥ = 0.021(1)) geometries. These values of the damping constant are considerably smaller than those previously reported in chemically.